Interactive textiles: Learning e-textiles with higher education art and design students - Kärnä-Behm, Jaana; Harjuniemi, Emmi (FormAkademisk, 2023)
The fusion of computing with textile materials has enhanced the interactive capabilities of textiles. Applying these electronic aspects of textile design is an evolving discipline. This study introduces a case study of teaching textile design in higher education with an interactive focus on art and design. We analysed projects and contents that appeared to be significant in the students’ processes as well as findings from the point of view of art and design pedagogy. Working on design education in multidisciplinary teams together with accessible technology was found rewarding. Knowing the basics of textile design is essential, but when developing e-textiles, interdisciplinary teachers are recommended. Moreover, creating positive experiences, circumstances and possibilities to continue the design process in the future is also important.